National Archives Ibadan and Archival Management in Nigeria: Challenges and Prospects - Okpanachi Solomon, Amodu (Kashere Journal of Humanities, Management and Social Sciences, 2022)
The National Archive, Ibadan (NAI) was established in 1954, on the backdrop of the loss (or fear loss) of the nation’s cultural heritages and colonial records in the form of documents to termites, rain, dust, rodents and other enemies of archives, to acquire and preserved records with archival values needed for historical understanding and reconstruction. Since its establishment, the institution had served as the custodian of the nation’s heritages in terms of records and valuables as evident in the quality and quantity of records that scholars and policy makers had utilized over the years. While the archives had served as a viable tool for scholars and the larger society, the contemporary states of the national archives in the form of numerous challenges is often overlooked by both the academia and policymakers and thus, threatening the prospect of the institution as the custodian of the nation’s heritage. From a critical analysis of the available primary and secondary data, the study argued that the challenges of the institution that include lack of acquisition, improper maintenance of holdings, acute shortage of staff, and lack of back-up and digitalization among others are largely due to the influence of African culture on record keeping, attitudes of the political class who viewed the institution as a dumping ground for ‘dead pasts,’ and the general society who perceived the institution as ‘government business.’ The study concluded that until there a change in attitudes by intervening in the contemporary states of NAI, the future of the past in the institution is in disarray.